The DEWI high-level architecture: Wireless sensor networks in industrial applications - Samano-Robles, Ramiro (2016)
This paper presents the high-level architecture (HLA) of the research project DEWI (dependable embedded wireless infrastructure). The objective of this HLA is to serve as a reference for the development of industrial wireless sensor and actuator networks (WSANs) based on the concept of the DEWI Bubble. The DEWI Bubble is defined here as a high-level abstraction of an industrial WSAN with enhanced interoperability (via standardized interfaces), technology reusability, and cross-domain development. This paper details the design criteria used to define the HLA and the organization of the infrastructure internal and external to the DEWI Bubble. The description includes the different perspectives, models or views of the architecture: the entity model, the layered model, and the functional view model (including an overview of interfaces). The HLA constitutes an extension of the ISO/IEC SNRA (sensor network reference architecture) towards the support of industrial applications. To improve interoperability with existing approaches the DEWI HLA also reuses some features from other standardized technologies and architectures. The HLA will allow networks with different industrial sensor technologies to exchange information between them or with external clients via standard interfaces, thus providing a consolidated access to sensor information of different domains. This is an important aspect for smart city applications, Big Data and internet-of-things (IoT).